Childbirth and parenting in horror texts : the marginalized and the monstrous - DiGioia, Amanda (Emerald Publishing, 2017)
This book examines childbirth and parenting in horror texts. By analysing new texts, and re-analysing commonly used texts with new feminist methodology, this study provides a unique contribution to the fields of gender and horror studies.
Keywords: Mothers in motion pictures.; Fathers in motion pictures.; Horror films.; Mothers in literature.; Fathers in literature.; Feminist films.; Feminist literature.; Horror in literature.; elektronické knihy; electronic books